Analisis Usahatani, Tataniaga dan Peran Kelembagaan Petani Teh Rakyat di Kabupaten Cianjur Sebagai Kawasan Perkebunan Teh Nasional - Nurhayat Indra (Jurnal Soshum Insentif, 2018)
This research is based on the phenomenon that the condition of tea plantation in Cianjur Regency is abandoned and damaged by the condition of underplanting population, whereas based on the Decree of the Minister of Agriculture of the Republic of Indonesia Number 46 / Kpts / PD.300 / 1/2015, Kabupaten Cianjur has designated as National Tea Plantation Area. The purpose of this research is to know: 1) Feasibility of Tea Tea farm in Cianjur District; 2) The condition of the tea community trading in Cianjur regency; and 3) The role of farmer institution in the development of Tea people in Cianjur Regency. The research was conducted in 3 (three) sub-districts of Cianjur People's Tea Center namely: Campaka, Takokak, and Sukanegara. The research methodology uses the descriptive and descriptive research with secondary and primary data sources collected through FGD. The result of this research are: (1) Farming Farming (agribusiness) of tea plantation in Cianjur Regency is not economically feasible; (2) Tatuiaga Teh shoot still using the village and / or village collectors trader channel, the margin obtained by farmers and traders of collectors is still reasonable, the added value of processing is still enjoyed quite large by the local green tea processor and dry / black tea; (3) Tea farmers' institutions in improving the bargaining position of farmers in the market have not been effective yet.